Perancangan dan Implementasi Sistem Manajemen Mutu ISO 9001:2015 PADA PT. X - Albert Lucano Effendi; Jani Rahardjo (Jurnal Titra, 2023)
PT. X is a heavy duty roller conveyor manufacturer based in Indonesia. The growing market and tense business competition are pushing the company to expand the business locally and internationally in order to survive. To expand the business network, the company must have a quality management system based on ISO 9001:2015. The company wants re-certification with more improved and sustained operation. The previous gap analysis shows that the company still hasn't managed to complete each clause to 100%. Lack of human resources impact on the implementation of ISO 9001:2015.